PERAN KEPUASAN KERJA DALAM MEMEDIASI PENGARUH STRESS KERJA, KOMPETENSI, DAN LINGKUNGAN KERJA TERHADAP PRESTASI KERJA PADA ASN DI BADAN KEPEGAWAIAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA (BKPSDM) SITUBONDO - Safira, Cinthia Bella; Karnadi, Karnadi; Tulhusnah, Lusiana (Jurnal Mahasiswa Entrepreneurship (JME), 2024)
The aim of this research is to analyze the influence of work stress, competence, work environment and job satisfaction on ASN work performance with compensation as intervening variable at the Personnel and Human Resources Development Agency of Situbondo Regency. By using the Partial Least Square (PLS) Structural equation model. The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that work stress has a significant positive effect on job satisfaction, competency has a positive but not significant effect on job satisfaction, work environment has a significant positive effect on job satisfaction, work stress has a positive but not significant effect on Achievement work, competence has a positive but not significant effect on work performance, work environment has a significant positive effect on work performance, job satisfaction has a significant effect on work performance, job stress has a positive but not significant effect on work performance through job satisfaction, competency has a positive but not significant effect on work performance through job satisfaction, the work environment has a positive but not significant effect on work performance through job satisfaction.